SCHOOL PRINCIPALS’ TACTICAL PLANNING STRATEGIES AND SCHOOL IMPROVEMENT IN PUBLIC SECONDARY SCHOOLS IN AGUATA LOCAL GOVERNMENT AREA, ANAMBRA STATE - Okeke, Ndidi Loretta (Int’l Journal of Education Research and Scientific Development, 2025)
This study investigated the crucial role of tactical planning in achieving meaningful and sustainable school improvement in public secondary schools within Aguata Local Government Area of Anambra State. It focused on understanding how, a short-term approach, can drive targeted actions and measurable progress in student achievement, teaching quality, and overall school improvement. Employing a descriptive survey design, data were gathered from 100 educators (principals, departmental heads, and teachers) using proportional stratified random sampling and a validated questionnaire. Reliability of the instrument was conducted using Cronbach’s alpha and a reliability coefficient of 0.81 was obtained. Descriptive statistics were used to analyze the collated data. Findings reveal that tactical planning strategies are vital for advancing school improvement through actionable steps that address local needs. However, challenges such as insufficient resources, ineffective communication, and weak monitoring systems hinder their success. The study recommends that policymakers in education should provide school leaders with adequate training, resources, and structural support to effectively implement tactical plans for lasting improvement.